Choice of GCC Construction Market Entry Mode - Al Sadi, Omar Jawdat (2015)
The international construction sector is one essential organ of the global economic body. While more construction companies target international construction markets, two related queries to both academicians and investors will be asked frequently: “What is the most appropriate mode to consider during entry?” and “On which basis entrant can choose this entry mode?”. This purpose of the study is to propose a framework to guide entrants for successful entry to GCC construction markets, therefore, the study investigated the decision making process of international contractors and examined the Gulf Cooperation Council (GCC) construction markets to identify the key factors that would influence a firm’s entry strategy. Those aims were achieved by extensive literatures studies which developed a preliminary framework to select entry modes based on their strategic effects, and a final framework indicating the most appropriate entry mode for each GCC market by implementing the decision making process model in context of GCC states. In order to collect the data, the study considered a combination of quantitative and qualitative approaches. Initially the entry mode data was collected from 86 international contractors’ web home pages, these contractors are listed as the most successful international contractors in each GCC state separately by MEED Projects (2015). And then further qualitative approach was considered to examine the proposed selection framework based on strategic effects in UAE construction market, interviews with carefully selected top management executives through face to face semi structured interviews have enabled the successful examining of proposed model. The study found that firms’ initial choice of a specific entry mode is a key strategic decision to ensure successful investment, as the option of entry mode adjustment is hard without incurring significant losses of time and money, moreover, it was found that construction unique characteristics imply different priorities than those in other industries to enter foreign markets. Furthermore, The study concluded that most of GCC markets require the entry using permanent modes, eventually a set of recommendations were introduced to facilitate the entry process and ensure successful entry to GCC construction markets.